SLCO1B1 variants as predictors of methotrexate-related toxicity in children with juvenile idiopathic arthritis. (4th May 2021) - Roszkiewicz, J; Michałek, D; Ryk, A; Swacha, Z; Szmyd, B; Smolewska, E
Abstract : Objectives : Methotrexate (MTX) administered at the dose 10–15 mg/m 2 is currently recommended as the first line therapy in most juvenile idiopathic arthritis (JIA) subtypes. Gastrointestinal side effects and hepatotoxicity are the most prevalent manifestations of MTX intolerance, frequently leading to discontinuation of otherwise effective treatment. Genetic variability within solute carrier organic anion transporter family member 1B1 ( SLCO1B1 ), encoding a hepatic MTX membrane transporter, has been associated with high-dose MTX efficacy and toxicity in paediatric patients with acute lymphoblastic leukaemia. The aim of our study was to determine the association between single-nucleotide polymorphisms in the SLCO1B1 gene (rs4149056, rs2306283) on the disease activity and presence of side effects of MTX therapy in patients with JIA. Method : The study recruited 100 children with JIA of all subtypes treated with MTX. Demographic and clinical parameters were collected at the baseline of MTX therapy and on a control visit 4–6 months after starting MTX. Genotyping was performed using genomic DNA isolated from peripheral blood samples. Results : In comparison to wild-type allele, SLCO1B1 rs4149056 CT/CC variant was significantly associated with higher odds ratio of MTX gastrointestinal side effects occurrence (OR=4.55, 95%CI 1.37-15.13; p=0.013). SLCO1B1 rs4149056 TT subjects were more likely than CT/CC individuals to develop hepatotoxicity (17.86% vs 4.76%, p = 0.046). Conclusion : SLCO1B1 rs4149056 may serve as a determinant of MTX treatment toxicity in children with JIA.